2021
DOI: 10.1007/s13668-021-00353-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Various Types of Intermittent Fasting (IF) on Weight Loss and Improvement of Diabetic Parameters in Human

Abstract: Purpose of Review A number of recent studies have suggested that intermittent fasting is as effective as traditional calorie restriction (CR) for weight loss and for cardioprotection. However, it is still unclear whether IF improves diabetes risk indicators as does CR. This review provides an overview of various patterns of intermittent fasting and shows the effect of intermittent fasting on human anthropometric such as excess body weight and biochemical parameters for example high glucose and fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 19 publications
(23 reference statements)
1
23
0
1
Order By: Relevance
“…Calorie restriction (CR) is a reduction in total caloric intake that does not result in malnutrition. This has consistently been found to result in decreased body weight and increased longevity in many species, including non-human primates [15]. Among overweight humans, shortterm CR (6-months) has been shown to significantly improve multiple cardiovascular risk factors, insulin sensitivity, and mitochondrial function.…”
Section: Intermittent Fasting Vs Caloric Restrictionmentioning
confidence: 99%
See 3 more Smart Citations
“…Calorie restriction (CR) is a reduction in total caloric intake that does not result in malnutrition. This has consistently been found to result in decreased body weight and increased longevity in many species, including non-human primates [15]. Among overweight humans, shortterm CR (6-months) has been shown to significantly improve multiple cardiovascular risk factors, insulin sensitivity, and mitochondrial function.…”
Section: Intermittent Fasting Vs Caloric Restrictionmentioning
confidence: 99%
“…Likely due to these physiological changes, clinical trials indicate CR may have a number of beneficial effects among overweight adults, in addition to weight loss. However, over the past several decades, obesity intervention trials have revealed that the vast majority of individuals experience difficulties sustaining daily CR for extended periods of time [15].…”
Section: Intermittent Fasting Vs Caloric Restrictionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though both dietary models can result in a decreased energy intake, the long-term adherence to CR is more difficult as compared with IF (Wegman et al, 2015 ; Lee et al, 2020 ). The most studied models of IF used CR on 2 days/week (5:2), alternate day energy restriction (energy restriction of 60–70% below estimated requirements) and time-restricted feeding (TRF) (timely restriction of calories intake during a specific time window during the day) (Nowosad and Sujka, 2021 ). Regardless of the model, IR and CR have been systematically associated with several beneficial effects in animal models and humans (Di Daniele et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%